Antimicrobial resistance of Campylobacter isolates from small scale and backyard chicken in Kenya. Issue 1 (December 2016) - Nguyen, Tuan; Hotzel, Helmut; Njeru, John; Mwituria, Joyce; El-Adawy, Hosny; Tomaso, Herbert; Neubauer, Heinrich; Hafez, Hafez
Abstract Background ThermophilicCampylobacter species are a major cause of bacterial foodborne diarrhoea in humans worldwide. Poultry and their products are the predominant source for human campylobacteriosis. Resistance ofCampylobacter to antibiotics is increasing worldwide, but little is known about the antibiotic resistance inCampylobacter isolated from chicken in Kenya. In this study, 35 suspectedCampylobacter strains isolated from faeces and cloacal swabs of chicken were tested for their susceptibility to seven antibiotics using a broth microdilution assay and molecular biological investigations. Results Overall, DNA of thermophilicCampylobacter was identified in 53 samples by PCR (34C. jejuni, 18C. coli and one mix of both species) but only 35Campylobacter isolates (31C. jejuni and 4C. coli ) could be re-cultivated after transportation to Germany. Isolates were tested for their susceptibility to antibiotics using a broth microdilution assay. Additionally, molecular biological detection of antibiotic resistance genes was carried out.C. jejuni isolates showed a high rate of resistance to nalidixic acid, tetracycline and ciprofloxacin of 77.4, 71.0 and 71.0 %, respectively. Low resistance (25.8 %) was detected for gentamicin and chloramphenicol. Multidrug resistance inC. jejuni could be detected in 19 (61.3 %) isolates. Resistance pattern ofC. coli isolates was comparable. Resistance to ciprofloxacin was confirmed by MAMA–PCR and PCR–RFLP in all phenotypically resistant isolates. Thetet (O) gene was detected only in 54.5 % of tetracycline resistantC. jejuni isolates. Thetet (A) gene, which is also responsible for tetracycline resistance, was found in 90.3 % ofC. jejuni and in allC. coli isolates. Thirteen phenotypically erythromycin-resistant isolates could not be characterised by using PCR–RFLP and MAMA–PCR. Conclusions To the best of our knowledge, this study is the first report about resistance to antibiotics in thermophilicCampylobacter originating from chicken in Kenya.Campylobacter spp. show a high level of resistance to ciprofloxacin, nalidixic acid and tetracycline but also a remarkable one to chloramphenicol and gentamicin and they are multidrug resistant. Resistance to antibiotics is a global public health concern. In Kenya, resistance surveillance needs further attention in the future. Efforts to establish at least a National Laboratory with facilities for performing phenotypic and genotypic characterization of thermophilicCampylobacter is highly recommended.